A case of Cameron lesion with severe iron deficiency anemia and review of literature - Abhishek Singhai; Rishabh Bose; Piyush Manoria (Babol University of Medical Sciences, 2022)
Background: Iron deficiency is the most common cause of anemia in many developing countries including India. Inadequate iron in diet, poor iron absorption, excessive bleeding, or chronic blood loss in the stool/ urine may be the cause. Cameron lesions are mucosa injuries of gastric body or fundus in the background of hiatal hernia. Case Presentation: Here we describe a case report of a 50-year-old female who presented to hospital with pain in abdomen. During laboratory workup she had severe anemia due to iron deficiency. Esophagogastroduodenoscopy revealed a large hiatal hernia with a superficial ulcer present in the hiatal pouch, the GE junction being 35 cm from the incisors. So, a hiatus hernia with a Cameron ulcer was identified as the culprit of iron deficiency anemia. Conclusion: The diagnosis of a Cameron lesion is difficult and sometimes ignored. In patients with anemia/bleeding, thorough surveillance of all stomach folds is essential, especially if a significant hiatal hernia is present.